2014
DOI: 10.1111/apv.12051
|View full text |Cite
|
Sign up to set email alerts
|

Assessing participation in cross‐border higher education in cities: Foreign education provision in Ho Chi Minh City

Abstract: One of the limitations of research on global educational mobility has been the primary classification of key participants – students and educational institutions – in national terms. This paper tests the challenges involved in such methodological nationalism by examining the provision of cross‐border education in one city. As Vietnam's commercial centre, Ho Chi Minh City (HCMC) has experienced rapid transformation over the past two decades as the country has moved steadily from a state‐directed to a more marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Despite distance education's inclusion in the overall body of transnational education modes, distance student voice is not adequately represented in its scholarship (Andrews & Tynan, 2010;Wilkins, 2016). By contrast, there is more work describing modes of delivery (e.g., Caruana & Montgomery, 2015;Francois, 2016;Knight, 2016;Wilkins & Huisman, 2012) and faculty experiences (e.g., Wilkins, Butt & Annabi, 2017;Ziguras & Pham, 2014). There are also investigations into the "international" student experience which may or may not fall into a transnational space given the conventional use of the term (see Erichsen & Bolliger, 2010;Habib, Johannesen, & Øgrim, 2014; Clegg & Reed, 2013;Selinger, 2004;Selwyn, 2011a;Selwyn, 2011b;Wilkins & Balakrishnan, 2013).…”
Section: Paradigm Shift: International To Transnationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite distance education's inclusion in the overall body of transnational education modes, distance student voice is not adequately represented in its scholarship (Andrews & Tynan, 2010;Wilkins, 2016). By contrast, there is more work describing modes of delivery (e.g., Caruana & Montgomery, 2015;Francois, 2016;Knight, 2016;Wilkins & Huisman, 2012) and faculty experiences (e.g., Wilkins, Butt & Annabi, 2017;Ziguras & Pham, 2014). There are also investigations into the "international" student experience which may or may not fall into a transnational space given the conventional use of the term (see Erichsen & Bolliger, 2010;Habib, Johannesen, & Øgrim, 2014; Clegg & Reed, 2013;Selinger, 2004;Selwyn, 2011a;Selwyn, 2011b;Wilkins & Balakrishnan, 2013).…”
Section: Paradigm Shift: International To Transnationalmentioning
confidence: 99%
“…The literature also indicates many transnational programs operating in Malaysia (see Arunasalam, 2016;Dobos, 2011;Sidhu & Christie, 2013;Wilkins et al, 2017), the Middle East (see Miller-Idriss & Hanauer, 2011;Wilkins et al, 2017), Vietnam (see Ziguras & Pham, 2014), Taiwan (see Yung- chi Hou, Morse & Wang, 2015), Indonesia (see Sutrisno & Pillay, 2013), Pakistan (see Kanu, 2005), Korea (see FSU, n.d.; IFEZ, n.d.; IGC, n.d., UCRX, n.d.) and Singapore (see Dobos, 2011) to list a few. Several programs located in Korea and known to this author are illustrated below.…”
Section: Real World Examplesmentioning
confidence: 99%
“…La educación transnacional, en ese proyecto, vendría a ser la formación de capital humano necesaria para el desarrollo económico de las empresas transnacionales. De esa manera, hubs de movilidad académica se instalan en países clave para los flujos financieros, sobre todo en la Asia oriental, en naciones como Singapur (COLLINS et al, 2014;WEISS;FORD, 2011), Malasia (ABD AZIZ; ABDULLAH, 2014; WEISS; FORD, 2011) y Hong Kong (GAO, 2014;WATERS;LEUNG, 2016;ZIGURAS;PHAM, 2014). La actuación de esas instituciones adopta el mismo proceso de branding que cualquier operación comercial, acogiendo o comprando nombres de universidades reconocidas para legitimarse y, así, controlar mercados (HEALEY; MICHAEL, 2014).…”
Section: Las Universidades Y La Producción De Internacionalizaciónunclassified
“…Despite distance education's inclusion in the overall body of transnational education modes, distance student voice is not adequately represented in its scholarship (Andrews & Tynan, 2010;Wilkins, 2016). By contrast, there is more work describing modes of delivery (e.g., Caruana & Montgomery, 2015;Francois, 2016;Knight, 2016;Wilkins & Huisman, 2012) and faculty experiences (e.g., Wilkins, Butt & Annabi, 2017;Ziguras & Pham, 2014). There are also investigations into the "international" student experience which may or may not fall into a transnational space given the conventional use of the term (see Erichsen & Bolliger, 2010;Habib, Johannesen, & Øgrim, 2014; Reed, 2013;Selinger, 2004;Selwyn, 2011a;Selwyn, 2011b;Wilkins & Balakrishnan, 2013).…”
Section: Paradigm Shift: International To Transnationalmentioning
confidence: 99%
“…Hou et al (2014) identified 511 transnational programs in China alone at both undergraduate and graduate levels. The literature also indicates many transnational programs operating in Malaysia (see Arunasalam, 2016;Dobos, 2011;Sidhu & Christie, 2013;Wilkins et al, 2017), the Middle East (see Miller-Idriss & Hanauer, 2011;Wilkins et al, 2017), Vietnam (see Ziguras & Pham, 2014), Taiwan (see Yung- chi Hou, Morse & Wang, 2015), Indonesia (see Sutrisno & Pillay, 2013), Pakistan (see Kanu, 2005), Korea (see FSU, n.d.; IFEZ, n.d.; IGC, n.d., UCRX, n.d.) and Singapore (see Dobos, 2011) to list a few. Several programs located in Korea and known to this author are illustrated below.…”
Section: Real World Examplesmentioning
confidence: 99%